Acute calculous cholecystitis complicated by a large anterior abdominal wall abscess - Bordo, Zanis; Berzina, Arta; Zeiza, Kaspars (International Surgery Journal, 2022)
We present a 74-year-old male patient with a rare case of acute calculous cholecystitis that was complicated by formation of a large anterior abdominal wall abscess due to neglection. The primary management consisted of antibiotic therapy and two consequent procedures of abscess drainage. Cholecystectomy was postponed due to the massive volume of the abscess which posed a great risk for complications if the patient were to be operated on at that point, therefore an elective open cholecystectomy was performed 3 months later. This case is a good example for the management of such a rare and interesting complication.